Thickness-Dependent Optical Properties and Exciton-Polariton States in Microcavities Based on Nanocrystalline SIC Films - Semenov, A.V.; Lopin, A.V.; Skorik, S.N. (Current Research Progress in Physical Science Vol. 8, 2025)
The optical properties of one-dimensional microcavity based on nanocrystalline SiC (nc-SiC) films containing nanocrystals of cubic and rhombohedric polytypes (R24 and R27, respectively) have been studied. It was revealed that resonance absorption maxima in absorption spectra measured at room temperature varied from 2.17 to 2.79 eV for the nc-SiC films 300 - 450 thick. The thickness dependences of the resonant absorption in microresonators based on heteropolytype nc-SiC films were explained using the model of exciton-polariton states in a one-dimensional SiC microresonator whose polytype changes with film thickness. It was established that the highest efficiency of polariton formation will be exhibited by excitons of those polytypes whose excitation energies will be close to the resonant photon modes of the microcavities. This causes spectral self-tuning of the microcavities to form exciton polaritons with the energy of excitons of the predominant polytype in nc-SiC films. Such properties of microresonators based on nanocrystalline SiC films can be extremely useful for future quantum technologies, such as frequency-tunable polariton lasers.